PEMANFAATAN TEKNOLOGI GAME ENGINE SEBAGAI MEDIA PROMOSI - Purnomo, Heri; Syamsul, Ludvi Nur (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
Education is important in our lives. Malang City is an education city with a total of 56 private universities. The high number of tertiary educational institutions has caused the competition to get prospective new students very tight. PPKIA STMIK Pradnya Paramita (STIMATA) is a private university located on Jl. LA. Sucipto 249 A Malang. To promote campus, STIMATA uses supporting media conventionally with brochures, banners or blocknote. But along with the development of the media promotion time is less attractive, impressed ordinary and less attractive to the public. From this problem the idea arises to use game engine technology as the STIMATA campus promotion media. This application was built using Blender and Unity3D with game-like appearance. In the main menu of this application there is a start button, information that serves to display information about the application and exit. The start button functions to run an application in the form of a game that contains a road button to run the user so that they can walk to see the campus starting from the gate to the STIMATA building on the 4th floor and the camera button used to look around the building by rotating virtually in 3D form. In this study, the introduction of the STIMATA campus promotion game engine application was successfully created and applied to Android mobile devices. This application can only be run on Android-based smartphones, with a minimum version of 4.0 (Ice Cream Sandwich).Keyword : Game engine,Promosi, Blender, Unity3D